Solvent-based Laminating Adhesives
By using a two-component solvent-based polyurethane adhesive composition, based on crystalline polyester-polycarbonate, the problem that the laminated adhesive in the prior art is difficult to achieve low oxygen permeability and gas barrier properties in flexible food packaging is solved. , achieving better oxygen barrier properties and packaging recyclability.
Patent Information
- Application Number
- CN202180035461.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-03
- Filing Date
- 2021-04-23
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-04-23
AI Technical Summary
Existing laminated adhesives are difficult to achieve low oxygen permeability and gas barrier properties in flexible food packaging, which affects the integrity of the packaging structure and food safety.
A two-component solvent-based polyurethane adhesive composition based on crystalline polyester-polycarbonate and comprises an isocyanate component and an isocyanate reactive component to form an adhesive laminate structure by combining and mixing.
It significantly improves oxygen barrier properties, reduces oxygen permeability, simplifies packaging structure, reduces costs, and makes food packaging recyclable.
Smart Images

Figure BDA0003943666120000101 
Figure BDA0003943666120000131 
Figure BDA0003943666120000132
Abstract
Description
Technical Field
[0001] The present invention relates to solvent-based laminating adhesive compositions; and methods of making such laminating adhesive compositions. Background Art
[0002] Laminating adhesives are used to bond different substrates together. Common uses of such bonded substrates are in flexible food packaging applications. Laminating adhesives are usually applied to the surface of two polymer substrate layers to form a bonding layer between the two substrate layers. The adhesive forms a bonding layer between the substrate layers to provide a firm bond between the two substrate layers. The substrate structure bonded by the adhesive helps to keep the packaging structure intact; and the safety and fixation of the food in the packaging structure. The growing demand in the flexible food packaging industry is for laminating adhesives with good gas barrier properties, such as reducing oxygen permeability through the layered structure of the flexible food packaging. Laminating adhesives for producing layered food packaging structures that show reduced oxygen permeability can potentially simplify the packaging structure, reduce the cost of use, and make the food packaging recyclable. Therefore, it is desirable to provide a laminating adhesive with enhanced oxygen barrier properties, such as an adhesive that exhibits low oxygen permeability compared to a standard adhesive. Specifically, it is desirable to provide a laminating adhesive based on a crystalline polyester-polycarbonate compound so that the adhesive has a gas barrier effect / characteristics. Summary of the invention
[0003] It is an object of the present invention to provide a laminating adhesive for flexible packaging applications, wherein the laminating adhesive has enhanced oxygen barrier properties compared to standard adhesives; and a process for producing such a laminating adhesive.
[0004] In one embodiment, the present invention is directed to a two-component solvent-based polyurethane adhesive composition, wherein the adhesive composition is based on a crystalline polyester-polycarbonate, and wherein the adhesive composition can be used to produce an adhesive laminate structure. The adhesive composition comprises, for example: (a) at least one isocyanate component; and (b) at least one isocyanate-reactive component, which includes at least one crystalline polyester-polycarbonate compound.
[0005] In another embodiment, the present invention is directed to a method of preparing the above-described adhesive composition.
[0006] In another embodiment, the present invention is directed to a multilayer laminate product comprising: (A) at least a first layer; (B) at least a second layer; and (C) at least one layer of the above-mentioned adhesive composition disposed between the first layer and the second layer; and wherein the adhesive composition is cured to bond the first layer to the second layer.
[0007] In yet another embodiment, the present invention is directed to a method for producing the above-described multi-layer laminate product.
[0008] In an even further embodiment, the present invention relates to a packaging product produced using the above-described multilayer laminated product. DETAILED DESCRIPTION
[0009] As used throughout this specification, the abbreviations given below have the following meanings, unless the context clearly indicates otherwise: "<" means "less than"; ">" means "greater than"; "≤" means "less than or equal to"; "≥" means "greater than or equal to"; @ means "at"; μm = micrometer, g = gram; mg = milligram; L = liter; g / cc = grams per cubic centimeter; mL = milliliter; g / mL = grams per milliliter; g / mol = grams per mole; g / m 2 = grams per square meter; ppm = parts per million; ppmw = parts per million by weight; rpm = revolutions per minute; m = meter; mm = millimeter; cm = centimeter; cm / min = centimeter per minute; min = minute; s = second; hr = hour; °C = degrees Celsius; N = Newton; mmHg = millimeter of mercury; psig = pounds per square inch; ccO2 / m 2 / day = cubic centimeters per oxygen [square meters-day]; N / 15mm = Newtons per 15 mm; kPa = kilopascals; % = percent, vol% = volume percent; and wt% = weight percent.
[0010] Unless otherwise indicated, all percentages, parts, ratios and similar amounts are defined by weight. For example, unless otherwise indicated, all percentages described herein are weight percentages (wt %).
[0011] Temperatures are in degrees Celsius (°C); and unless otherwise indicated, "ambient temperature" and / or "room temperature" refers to temperatures between 20°C and 25°C.
[0012] The present invention relates to novel two-component solvent-based polyurethane adhesive compositions, wherein the adhesive composition is based on crystalline polyester-polycarbonate, and wherein the adhesive composition can be used to produce adhesive laminate structures. In a broad embodiment, the adhesive composition of the present invention comprises: (a) at least one isocyanate component; and (b) at least one isocyanate-reactive component, which includes at least one crystalline polyester-polycarbonate compound.
[0013] To prepare a two-component adhesive composition, the method includes: providing a first component including an isocyanate component, namely component (a); providing a second component including a polyol component, namely component (b); and then combining or mixing component (a) and component (b) to form a two-component adhesive system or composition.
[0014] The isocyanate component (component (a)) of the present invention may include one or more isocyanate compounds. For example, the isocyanate compound may include aliphatic-based isocyanates, aromatic-based isocyanates, and mixtures thereof. Aliphatic-based polyisocyanates are isocyanates that do not contain aromatic rings. Examples of suitable aromatic isocyanates that can be used in the present invention include, but are not limited to, hexamethylene diisocyanate (HDI); diisocyanate dicyclohexylmethane (HDI); 12 MDI); xylene diisocyanate (XDI); 1,4- or 1,3-bis(isocyanatemethyl)cyclohexane (H6XDI); tetramethylxylene diisocyanate; dimers, trimers and derivatives and mixtures of two or more thereof.
[0015] Aromatic-based isocyanates useful in the present invention may include, for example, one or more polyisocyanate compounds, including, but not limited to, for example, 1,3- and 1,4-phenylene diisocyanates; 1,5-naphthylene diisocyanate; 2,6-toluene diisocyanate (2,6-TDI); 2,4-toluene diisocyanate (2,4-TDI); 2,4′-diphenylmethane diisocyanate (2,4′-MDI); 4,4′-diphenylmethane diisocyanate (4,4′-MDI); polymeric isocyanates; and mixtures of two or more thereof.
[0016] In a preferred embodiment, the isocyanate component useful in the present invention may be an XDI-based polyisocyanate; an HDI-based polyisocyanate; an MDI-based polyisocyanate; a TDI-based polyisocyanate; and mixtures thereof.
[0017] Examples of some commercial isocyanate components that can be used in the present invention may include D-110N and D-120N (all available from Mitsui Chemical); N 3300, Quix 175 and E 2200 / 76 (both available from The Covestro Company); and ISONATE TM 125M, ADCOTE TM L76-204, COREACTANT CT and CATALYST F (all available from The Dow Chemical Company); and mixtures thereof.
[0018] The isocyanate has an average functionality of greater than 2 isocyanate groups per molecule. In one embodiment, for example, the isocyanate may have an average functionality of from 2.1 to 4.0.
[0019] Compounds having isocyanate groups, such as the isocyanate component (a) of the present invention, are also characterized by the weight percentage of isocyanate groups (NCO) based on the total weight of the compound. The weight percentage of isocyanate groups is referred to as "NCO%" and is measured according to ASTM D2572-97. In one embodiment, the NCO content of component (a) is 7% or more; and in another embodiment, 10% or more. In another embodiment, the NCO content of component (a) is 30% or less; and in another embodiment, 25% or less.
[0020] The amount of the isocyanate component used in the method of the present invention is, for example, 2 wt% to 40 wt% in one embodiment, 3 wt% to 30 wt% in another embodiment, and 4 wt% to 20 wt% in yet another embodiment.
[0021] The isocyanate-reactive component (component (b) (or B-side component)) of the present invention includes an isocyanate-reactive composition, which is at least one crystalline polyester-polycarbonate compound. In a preferred embodiment, the at least one crystalline polyester-polycarbonate compound may contain other compounds to form an isocyanate-reactive composition. For example, the isocyanate-reactive composition can be a mixture, combination or blend of the following items: (b1) a predetermined amount of at least one crystalline polyester-polycarbonate compound; (b2) a predetermined amount of at least one acrylic polymer compound; and (b3) a predetermined amount of at least one solvent. The mixture or blend of the above three components (b1) to (b3) forms an isocyanate-reactive component (b) mixed with the isocyanate component (a). A crystalline polyester-polycarbonate-based polyurethane adhesive composition for producing an adhesive laminate structure is formed by mixing component (a) with component (b).
[0022] In one embodiment, component (a) may be mixed with component (b) in a weight ratio of 4:100 to 30:100; in another embodiment at 5:100 to 25:100; and in yet another embodiment at 6:100 to 20:100.
[0023] Crystalline polyester-polycarbonate diol is a compound having a structure of a polyester functional group, a polycarbonate functional group, and a hydroxyl end-capping group; and is solid within a temperature range including a range of 10°C to 40°C. Generally speaking, the polyester-polycarbonate diol of the present invention is the reaction product of: (bi) at least one polyester polyol precursor; and (bii) at least one polycarbonate polyol precursor. For example, the polyester polyol precursor can be selected from the group consisting of: polyester resins based on ethylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, adipic acid, azelaic acid, sebacic acid, terephthalic acid, and combinations thereof. For example, the polycarbonate polyol precursor can be selected from the group consisting of: polycarbonate resins based on ethylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, alkylene carbonates, diaryl carbonates, dialkyl carbonates, and combinations thereof.
[0024] Examples of suitable crystalline polyester-polycarbonate diols that can be used in the present invention include, but are not limited to: (1) a reaction product of poly(1,4-butylene glycol-adipic acid) and poly(1,4-butylene glycol-dimethyl carbonate); (2) a reaction product of poly(1,6-hexanediol-adipic acid) and poly(1,4-butylene glycol-dimethyl carbonate); and (3) a mixture of two or more thereof. Preferred crystalline polyester-polycarbonate diols that can be used in the present invention are crystalline polyester-polycarbonate diols having a melting temperature of 35° C. to 60° C. and a molecular weight of 500 g / mol to 3,500 g / mol.
[0025] Examples of some commercial polyester diol compounds that can be used in the present invention may include, for example, BESTER TM 86 (available from The Dow Chemical Company); PC-105P-110, PC-102P-110 and PC-205P-056 (both available from Stepan Company); and mixtures thereof.
[0026] Examples of some commercial polycarbonate diol compounds that can be used in the present invention may include, for example UH-100, UH-200 and UH-300 (both available from UBE Industries, Inc.).
[0027] The amount of the crystalline polyester-polycarbonate compound (component (b)) used in the present invention is, for example, 10 to 50 wt % in one embodiment, 15 to 45 wt % in another embodiment, and 20 to 40 wt % in yet another embodiment.
[0028] As described above, a preferred embodiment of the present invention includes an isocyanate-reactive composition mixture, combination or blend of: (bi) a predetermined amount of at least one crystalline polyester-polycarbonate compound; (bii) a predetermined amount of at least one acrylic polymer compound; and (biii) a predetermined amount of at least one solvent.
[0029] At least one crystalline polyester-polycarbonate compound, component (bi), useful in forming the isocyanate-reactive composition blend is described above.
[0030] At least one acrylic polymer compound (component (bii)) useful in the present invention is a flow modifier or flow control agent, which is commonly used in powder coatings to control sag and reduce orange peel. Flow modifiers help control the interfacial tension and surface tension of the adhesive.
[0031] The flow modifiers useful in the present invention may include one or more common flow modifiers. Examples of flow modifiers include low glass transition temperature acrylics such as polylauryl acrylate; polybutyl acrylate; poly(2-ethylhexyl) acrylate; poly(ethyl acrylate-2-ethylhexyl acrylate); polylauryl methacrylate; and acrylic copolymers made from two or more monomers including methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, methyl methacrylate, acrylic acid, methacrylic acid, styrene, vinyl acetate, butadiene, etc.; and mixtures thereof. Other flow modifiers useful in the present invention may include silicon-containing polymers and fluorinated polymers such as esters of polyethylene glycol, esters of polypropylene glycol, fluorinated fatty acids, and mixtures thereof.
[0032] The amount of acrylic polymer compound used to prepare the isocyanate-reactive co-reactant (component (b)) of the process of the present invention is, for example, 0.05 wt % to 4 wt % in one embodiment, 0.1 wt % to 3 wt % in another embodiment, and 0.2 wt % to 2 wt % in yet another embodiment.
[0033] At least one solvent compound (component (biii)) of the present invention may include one or more compounds, including, for example, ethyl acetate, methyl ethyl ketone, propyl acetate, toluene and mixtures thereof. Other conventional solvents known to those skilled in the art may also be used. In a preferred embodiment, solvent compounds useful in the present invention may include, for example, ethyl acetate, methyl ethyl ketone and mixtures thereof.
[0034] The amount of the solvent compound used to prepare the isocyanate-reactive co-reactant (component (b)) of the present invention is, for example, 10 to 90 wt% in one embodiment, 30 to 85 wt% in another embodiment, and 50 to 80 wt% in yet another embodiment.
[0035] In some embodiments, the adhesive compositions of the present invention may include one or more optional additives, including but not limited to, for example, tackifiers, catalysts, plasticizers, rheology modifiers, adhesion promoters, antioxidants, fillers, colorants, surfactants, solvents, and combinations of two or more thereof.
[0036] The amount of optional components that can be used in the adhesive composition may be, for example, 0 wt % to 3 wt % in one embodiment, 0 wt % to 2 wt % in another embodiment, and 0.01 wt % to 1 wt % in yet another embodiment.
[0037] Generally, the method for preparing the laminating adhesive composition comprises the following steps: (I) synthesizing a crystalline polyester-polycarbonate diol by reacting at least one polyester polyol with at least one polycarbonate polyol at a temperature of 180°C to 250°C for a period of at least 2 hours to 8 hours; (II) melting the crystalline polyester-polycarbonate diol from step (I) at a temperature of 50°C to 70°C (the crystalline polyester-polycarbonate diol is solid at a temperature of 15°C to 40°C); (III) pouring the molten diol from step (II) into a reactor, wherein the reactor has been preheated at a temperature of 50°C to 60°C; (II) charging the reactor with a solvent and any other optional additives; (IV) mixing all the components in the reactor by stirring until a resulting uniformly mixed, completely clear solution is formed; and (V) removing the resulting completely clear solution from the reactor.
[0038] A multilayer laminated product can be formed, which includes a layer of a solvent-based polyurethane adhesive composition based on a crystalline polyester-polycarbonate of the present invention. Any number of layers can be used to form a laminated product. In a preferred embodiment, the laminate is formed by the following steps: applying the adhesive composition to at least one of two substrate layers (for example, these substrates can be made of the same material or made of different materials); combining these substrates together so that the adhesive composition is disposed between the surfaces of the two substrates as a layer; and then curing the adhesive composition to form a bonding layer between the two substrates. Generally speaking, each of the two substrates can include, for example, two separate polymer films. As used herein, a "film" is any layer structure that is 0.5 mm or less in one dimension of the layer structure; and is 1 cm or greater in the other two dimensions of the layer structure. A "polymer film" is a film made of a polymer or a polymer mixture. A polymer film is generally composed of 80% by weight or more of one or more polymers.
[0039] Suitable substrates for forming laminated structures include films, such as paper, woven fabrics and nonwoven fabrics, polymer films, metal-coated (metallized) polymer films and combinations thereof. Substrates are stacked to form laminated structures, wherein one or more of these substrates are adhered together according to the adhesive composition of the present invention.
[0040] In a preferred embodiment, a multilayer laminate product prepared using the adhesive composition of the present invention includes: (A) at least a first layer; (B) at least a second layer; and (C) at least one layer of the adhesive composition disposed between the first layer and the second layer; wherein the adhesive is cured to bond the first layer to the second layer.
[0041] In a general embodiment, the multilayer laminated product can be two or more film substrates or film layers combined with an adhesive composition. In some embodiments, the laminated product is a laminated film structure comprising a first film layer, a second film layer, and a barrier adhesive layer disposed between the first film layer and the second film layer. For example, in a preferred embodiment, the multilayer laminated product can be made of three layers including the following items: a first film layer (or outer layer), a second film layer (or inner layer), and a bonding layer, the bonding layer comprising an adhesive composition disposed between the first layer and the second layer.
[0042] The 3-layer laminated product of the present invention may have a layered structure of A / B / A, wherein A represents a first layer and a second layer having the same material, and wherein B represents a bonding layer having an adhesive composition. Although a 3-layer laminated film product is referenced herein, the present invention includes a multilayer laminated member having any number of film layers, provided that at least one layer of the multilayer film member is a bonding layer having an adhesive composition, wherein the bonding layer has appropriate gas barrier properties. As described above, the structure of the multilayer film member may be A / B / A, wherein the two layers represented by A are made of the same polymer material; or the structure of the multilayer film member may be A / B / C, wherein C represents a film layer made of a material different from the A layer. Alternatively, the structure of the multilayer film member may be any combination of A, B, and C layers that are apparent to a technician in the field of laminated manufacturing.
[0043] The first layer of the laminated product of the present invention can be made of one or more materials, including, for example, polyethylene, polypropylene, polyethylene terephthalate, polyamide, polystyrene, cyclic olefin copolymer, polyvinyl chloride, styrene butadiene, etc. In a preferred embodiment, the material that can be used for the first layer of the present invention can be polypropylene, polyethylene, and combinations thereof. Examples of some commercial materials that can be used for the first layer of the present invention can include, for example, biaxially oriented polypropylene (available from FILMTECH); and polyethylene (available from Berry Plastics); and mixtures thereof. In another preferred embodiment, the first film layer can be made of, for example, polypropylene having a density of 0.89 g / cc to 0.92 g / cc.
[0044] The thickness of the first layer used in the laminated product of the present invention is, for example, 10 μm to 200 μm in one embodiment, 15 μm to 150 μm in another embodiment, and 20 μm to 125 μm in yet another embodiment.
[0045] As mentioned above, the second layer of the laminated product of the present invention can be made of the same material as the first layer, which has the advantage of being more easily recyclable. In another embodiment, the second layer can be made of one or more materials different from the first layer.
[0046] When the second layer of the laminated product is made of a different polymer from the first layer, the second layer may include, for example, polyethylene, polypropylene, polyethylene terephthalate, polyamide, polystyrene, cyclic olefin copolymer, polyvinyl chloride, styrene butadiene, and mixtures thereof. In a preferred embodiment, the material for the second layer that can be used in the present invention may be polyethylene, polypropylene, and mixtures thereof. Examples of some commercial materials that can be used in the second layer of the present invention may include, for example, polyethylene (available from Berry Plastics); and biaxially oriented polypropylene (available from FILMTECH); and mixtures thereof. In another preferred embodiment, when different from the first layer, the second film layer may be made of, for example, polyethylene having a density of 0.915 g / cc and a value of 0.967 g / cc.
[0047] The thickness of the second layer used in the film of the present invention is, for example, 10 μm to 200 μm in one embodiment, 15 μm to 150 μm in another embodiment, and 20 μm to 125 μm in yet another embodiment.
[0048] Generally speaking, a method for producing a multilayer laminate product as described above comprises the following steps:
[0049] (I) applying the adhesive composition of the present invention to at least a portion of the surface of the first layer and / or the second layer;
[0050] (II) contacting the first layer with the second layer such that the adhesive is disposed between the first layer and the second layer; and
[0051] (III) curing the adhesive to form a multi-layer laminate product, comprising bonding the first layer to the second layer via the cured adhesive.
[0052] The laminated film structures of the present invention include films made by bonding polymers together using a barrier adhesive composition instead of a standard adhesive composition, while the laminated film structures of the present invention still achieve similar or enhanced barrier properties. One of the advantageous properties exhibited by the laminated products made by the above-described methods of the present invention may include, for example, that the laminate has an improved (i.e., reduced) oxygen permeability (OTR). In some embodiments, the laminated film structure has no more than 750 cubic centimeters of oxygen per [square meter-day] (abbreviated as "ccO2 / m 2 / day") and is measured according to ASTM method D3985.
[0053] Because laminated film structures can be designed with a variety of layer materials, number of layers, film thicknesses, and other properties, the OTR of a particular laminated structure will depend on, for example, the various properties of the first and second layers. By way of illustration, and not limitation, in one embodiment, the OTR of a laminated structure of the present invention is generally 15% lower than a laminate using a standard adhesive composition; in another embodiment, 25% lower than a laminate using a standard adhesive composition; and in yet another embodiment, 50% lower than a laminate using a standard adhesive composition. In yet another embodiment, the OTR of a laminated structure of the present invention is 10% to 95% lower than a laminate using a standard adhesive composition.
[0054] The laminates prepared as described above can be used, for example, in flexible packaging applications; and in home and personal care applications. In a preferred embodiment, the laminate is used to prepare a multilayer laminated structural product or article, such as a package, bag or container for packaging food. In a preferred embodiment, the laminate is made of two layers of polymer film, wherein the adhesive layer is disposed between the two film layers, and the two film layers bond the two polymer films together. The method of preparing an article, such as a food packaging article, can be performed by a person skilled in the art of food packaging manufacturing.
[0055] As described above, by using the barrier adhesive layer of the present invention in place of a standard adhesive, the permeability of oxygen through the laminated structure is reduced; therefore, articles prepared using the laminates described above will have the same advantageous gas barrier properties, such as the improved (i.e., reduced) OTR exhibited by the laminates described above.
[0056] Additionally, the ABA structure possessed by the multilayer laminate may advantageously be a simple, easy to manufacture structure, and may also advantageously be recyclable, such that food packaging made from the laminate is environmentally friendly.
[0057] Example
[0058] The following examples are provided to further illustrate the present invention in detail but should not be construed as limiting the scope of the claims. Unless otherwise indicated, all parts and percentages are by weight.
[0059] The various materials or components used in the examples of the present invention (Inv.Ex.) and comparative examples (Comp.Ex.) are explained as follows:
[0060] MOR-FREE TM C33 is an aliphatic based isocyanate and is commercially available from The Dow Chemical Company (Dow).
[0061] ADCOTE TM 577 is an isocyanate terminated compound and is commercially available from Dow.
[0062] ADCOTE TM 577B is a hydroxyl terminated compound and is commercially available from Dow.
[0063] BESTER TM 86 is a poly(butylene glycol monoadipate) having a molecular weight (Mw) of 1,000, a melting point of about 50°C, and an OHN of 112; and is commercially available from Dow.
[0064] is an acrylic copolymer resin useful as a flow modifier and is commercially available from Allnex Corporation.
[0065] DOWTHERM TM TUNE(R) is a heat transfer fluid and is commercially available from Dow.
[0066] TPT (tetraisopropyl titanate) is a highly reactive organoalkoxy titanate having a 100% active content and acts as a Lewis acid catalyst; and is commercially available from Dorf Ketal.
[0067] "BOPP" stands for biaxially oriented polypropylene. BOPP is a film with a thickness of 20 μm and is commercially available from Filmtech.
[0068] Polyester-polycarbonate resin
[0069] Synthesis Example 1-1, Preparation of 4-Butanediol-Carbonate Resin ("PC-1")
[0070] In this Synthesis Example 1, a 1,4-butanediol-carbonate resin (herein "PC-1") having a molecular weight of about 2,000 was prepared using the components described in Table 1 and the following procedure:
[0071] Table I - Preparation of polycarbonate resin (PC-1) (Mw = 2,000)
[0072]
[0073] A 114 liter (L) 316L stainless steel vessel (reactor) was used. The reactor had an inner diameter of 20 inches (50.8 cm) and was equipped with internal baffles, a variable speed 12-inch (30.5 cm) turbine impeller, a sparging ring, a closed loop system consisting of a hybrid DOWTHERM* system with separate hot and cold loops and a 24-inch (61 cm) packed column. 67,958.0 g of butanediol (BDO) was added to the reactor and heated to 150 degrees Celsius (°C) while purging with nitrogen (N2) to make the reactor inert and remove water present in the butanediol. TPT catalyst (21.6 g) was added to the reactor. Dimethyl carbonate (DMC) was also added to the reactor using a flow meter and a control valve over a period of 6 to 8 hours, maintaining the column temperature at 65°C. After the addition of DMC was complete, the temperature of the reactor was increased to 195°C, and the progress of the reaction in the reactor was tracked by measuring the OH number and 1H-NMR of the reaction mixture for end group analysis. After 8 hours at 195°C, the OH number of the reaction mixture was found to be 30.7, wherein the carbonate end group was 25 percent (%) as determined by 1H-NMR; and the temperature of the reactor was reduced to 150°C; and 1,860 g of BDO was added to the reaction mixture. Then, the temperature of the reaction mixture was increased to 195°C; and after 8 hours of reaction, the hydroxyl number of the resulting reaction product was found to be 54 mg KOH / g, wherein the carbonate end group was <1%. The resulting carbonate resin had the following final physical properties: OHN was 54 and the molecular weight (Mw) was 1,960.
[0074] Synthesis Example 2-1, Preparation of 4-Butanediol-Carbonate Resin (hereinafter referred to as "PC-2")
[0075] In this Synthesis Example 2, a 1,4-butanediol-carbonate resin (herein "PC-2") having a molecular weight of about 1,000 was prepared using the components described in Table II and the following procedure:
[0076] Table II - Preparation of Polycarbonate Resin PC-2
[0077] <![CDATA[ Component No. ]]> <![CDATA[ Monomer / Intermediate ]]> <![CDATA[ Injection(g) ]]> 4 1,4-Butanediol-carbonate with Mw of 2,000 (PC-1 from Synthesis Example 1) 1,200 5 1,4-Butanediol 60.5
[0078] A polycarbonate resin was prepared by charging components 4 and 5 described in Table II into a 2L 4-neck flask equipped with a Teflon stirring blade. The resulting mixture in the flask was heated to 210° C. while stirring. The stirred mixture was then maintained at 210° C. for 4 hours under a nitrogen purge. After 4 hours, the resulting resin had the following final physical properties: OHN was 112.0 and Mw was 1,000.
[0079] Polyester-polycarbonate resin
[0080] Synthesis Example 3 - Preparation of Polyester-Polycarbonate Polyol 1 (PE-PC-1)
[0081] In this Synthesis Example 3, a polyester-carbonate-polyol resin (herein "PE-PC-1") having a molecular weight of about 1,000 was prepared using the components described in Table III and the following procedure:
[0082] Table III - Formulation for Preparation of MW 1000 Polyester-Polycarbonate Polyol 1 Resin (PE-PC-1)
[0083] <![CDATA[ Component No. ]]> <![CDATA[ Monomer / Intermediate ]]> <![CDATA[ Injection(g) ]]> 6 <![CDATA[BESTER TM 86]]> 900.0 7 1,4-T diol-carbonate with Mw of 2,000 (PC-1 from Synthesis Example 1) 100.0 8 1,4-Butanediol 4.24
[0084] PE-PC-1 resin was prepared by charging components 6 to 8 into a 2L 4-neck flask equipped with a Teflon stirring blade. The resulting mixture in the flask was heated to 210°C while stirring, and the stirred mixture was maintained at 210°C for 4 hours under a nitrogen purge. After 4 hours, the resulting resin had the following final physical properties: OHN of 112.0, Mw of 1,000, and a melting temperature of 43°C.
[0085] Synthesis Example 4 - Preparation of Polyester-Polycarbonate Polyol 2 Resin (PE-PC-2)
[0086] In this Synthesis Example 4, a polyester-carbonate-polyol resin having a molecular weight of about 1,000 (herein "PE-PC-2") was prepared using the components described in Table IV and using the following procedure:
[0087] Table IV - Formulation for Preparation of MW 1000 Polyester-Polycarbonate Polyol 2 Resin (PE-PC-2)
[0088] <![CDATA[ Component No. ]]> <![CDATA[ Monomer / Intermediate ]]> <![CDATA[ Injection(g) ]]> 9 <![CDATA[BESTER TM 86]]> 750.0 10 1,4-T diol-carbonate with Mw of 2,000 (PC-1 from Synthesis Example 1) 250.0 11 1,4-Butanediol 11.90
[0089] PE-PC-2 resin was prepared by charging components 9 to 11 into a 2L 4-neck flask equipped with a Teflon stirring blade. The resulting mixture in the flask was heated to 210°C while stirring. The stirred mixture was then maintained at 210°C for 4 hours under a nitrogen purge. After 4 hours, the resulting resin had the following final physical properties: OHN of 112.0, Mw of 1,000, and a melting temperature of 40°C.
[0090] Synthesis Example 5 - Preparation of Polyester-Polycarbonate Polyol 3 (PE-PC-3)
[0091] In this Synthesis Example 5, a polyester-carbonate-polyol resin (herein "PE-PC-3") having a molecular weight of about 1,000 was prepared using the components described in Table V and the following procedure:
[0092] Table V - Formulations for Preparation of MW 1000 Polyester-Polycarbonate Polyol 3 Resin (PE-PC-3)
[0093]
[0094] PE-PC-3 resin was prepared by charging components 12 and 13 into a 2L 4-neck flask equipped with a Teflon stirring blade. The resulting mixture in the flask was heated to 210°C while stirring. The stirred mixture was then maintained at 210°C for 4 hours under a nitrogen purge. After 4 hours, the resulting resin had the following final physical properties: OHN of 112.0, Mw of 1,000, and a melting temperature of 42°C.
[0095] Isocyanate co-reactant
[0096] General Procedure for the Preparation of Isocyanate Coreactants (CR)
[0097] Three isocyanate-reactive co-reactants (CR-1, CR-2, and CR-3) were prepared using the compositions described in Table VI in the following steps: using the crystalline polyester-polycarbonate polyol compounds described above in Synthesis Examples 3 to 5. The polyester-polycarbonate polyol was first melted in an oven at 60° C.; then, the molten crystalline or amorphous polyester-polycarbonate polyol compound was mixed with ethyl acetate and Modaflow at 60° C. for 1 hour to form the various isocyanate-reactive compositions described in Table VI.
[0098] Table VI - Co-Reactant (CR) Composition
[0099]
[0100] Adhesive formulations
[0101] Examples 1 to 3 and Comparative Example A
[0102] General Procedure for Preparing Adhesive Formulations
[0103] The adhesive formulations described in Table VII were prepared by mixing the components listed in Table VII under the following conditions:
[0104] Table VII describes the relevant ingredients used to prepare the adhesive formulation, isocyanate reactive component and isocyanate component. Using the adhesive of Example 1 of the present invention as an illustration for the preparation of the adhesive formulation sample, about 2,541 g of the isocyanate reactive component (component B), about 459 g of the isocyanate component (component A) were charged into a plastic container. The materials were mixed for 30 minutes using a mechanical mixer at room temperature (about 25° C.) to obtain the formulated adhesive of Example 1 of the present invention.
[0105] Table VII describes the adhesive formulations for selected examples, where all adhesives have the same amount of excess isocyanate.
[0106] Table VII - Adhesive Formulations
[0107]
[0108] Coated laminate
[0109] Examples 4 to 6 and Comparative Example B
[0110] General Procedure for Preparing Coated Laminates
[0111] As mentioned above, the polyurethane adhesive formulations of Examples 1 to 3 of the present invention and Comparative Example A were prepared using the general procedure for preparing adhesive formulations and the formulation ingredients described in Table VII. Then, the adhesive formulation was first coated on a primary substrate by a gravure cylinder. The coated film was then passed through three partition ovens to dry the coated film and remove the ethyl acetate solvent. The coated film was then clamped on another substrate under a heated steel roller at 90°C, and the nip pressure was set to 40PSI (275.8kPa). The laminated structure was then placed in a temperature controlled chamber to cure for 7 days at 23°C and 50% relative humidity (RH). The adhesive coating amount on each laminate in these laminates was then measured and recorded.
[0112] Examples 4 to 6
[0113] Coated laminates were produced using the polyurethane adhesive compositions of Inventive Examples 1 to 3 described in Table VII above and the general procedure for preparing coated laminates as described above. The adhesive coating amount of each of the resulting laminates of Inventive Examples 4 to 6 was 3.5 g / m 2 .
[0114] Comparative Example B
[0115] In this Comparative Example B, the polyurethane adhesive formulation of Comparative Example A described in Table VII above was used to produce a coated laminate using the same general procedure as described above for preparing the coated laminate, except that the coated laminate was placed in a temperature controlled chamber to cure at 23° C. and 50% RH for 7 days. The adhesive coating weight of the resulting laminate of Comparative Example B was 3.5 g / m 2 .
[0116] Laminate / Adhesive Properties
[0117] The following tests: 90° T-peel test and oxygen transmission rate (OTR) measurement were performed using the coated laminate samples prepared above. The results of the tests are described in Table VIII.
[0118] 90° T-peel test
[0119] The 90° T-peel test was performed on laminate samples consisting of two films: a primary film and a secondary film adhered together with an adhesive. The laminate samples were cut into 15 mm wide strips and each of these samples was weighed on a Thwing Albert equipped with a 50 N load cell. TMPull on QC-3A peel tester.Pull the laminate sample at a rate of 4 inches / min (10cm / min) with a peel tester on a 15mm strip.When the two films in the laminate are separated (peeled off), the average value of the force during pulling is recorded.If one of the films is tensioned or broken, the maximum force or breaking force is recorded.The final value of the laminate sample is the average value of the three individual sample strips tested.Failure mode (FM) or failure mode (MOF) is recorded as follows: AS (adhesive split) or cohesive failure, which shows that the adhesive is present on both the primary film and the secondary film.
[0120] Oxygen Transmission Rate (OTR) Measurement
[0121] The oxygen transmission rate (OTR) of the formed laminates was measured using a MOCON OXTRAN 2 / 21 following the procedure described in ASTM method D3985 ("Standard Test Method for Transmission Rate of Oxygen Through Plastic Film and Sheeting Using a Coulometric Sensor"). OTR data is reported in standard units of "cc / (m 2 The conditions used for testing to obtain OTR measurements were 23°C and 85% relative humidity (RH).
[0122] Table VIII - Laminate Property Measurements
[0123]
[0124] As can be seen from the data described in Table VIII, the laminates of Inventive Examples 4, 5 and 6 coated with the adhesive formulations containing crystalline polyester-polycarbonate of Inventive Examples 1, 2 and 3, respectively, exhibited improved OTR barrier properties compared to the laminate of Comparative Example B coated with the adhesive formulation containing a non-crystalline polyester backbone.
Claims
1. A crystalline polyester-polycarbonate-based polyurethane adhesive composition for producing an adhesive laminate structure, the polyurethane adhesive composition comprising: (a) at least one isocyanate component, wherein the at least one isocyanate component is selected from the group consisting of: polyisocyanates based on xylene diisocyanate; polyisocyanates based on hexamethylene diisocyanate; polyisocyanates based on diphenylmethane diisocyanate; polyisocyanates based on toluene diisocyanate; and (b) at least one isocyanate-reactive component, the at least one isocyanate-reactive component comprising a blend of: (bi) 15 wt % to 45 wt % of at least one crystalline polyester-polycarbonate diol compound, based on the total weight of the isocyanate-reactive components; (bii) 0.05 wt % to 4 wt % of at least one acrylic polymer compound, based on the total weight of the isocyanate-reactive component; and (biii) 10 wt % to 90 wt % of at least one solvent, based on the total weight of the isocyanate-reactive component. 2 . The adhesive composition according to claim 1 , wherein the weight ratio of component (a) to component (b) is 4:100 to 30:
100.
3. The adhesive composition according to claim 1, wherein the crystalline polyester-polycarbonate compound is a reaction product of: (bi) at least one polyester polyol precursor; and (bii) at least one polycarbonate polyol precursor.
4. The adhesive composition of claim 3, wherein the polyester polyol precursor is selected from the group consisting of polyester resins based on ethylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, adipic acid, azelaic acid, sebacic acid, terephthalic acid, and combinations thereof.
5. The adhesive composition of claim 3, wherein the polycarbonate polyol precursor is selected from the group consisting of polycarbonate resins based on ethylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, alkylene carbonates, diaryl carbonates, dialkyl carbonates, and combinations thereof.
6. The adhesive composition according to claim 1, wherein the at least one crystalline polyester-polycarbonate compound is selected from one or more of (1) a reaction product of poly(1,4-butylene glycol-adipic acid) and poly(1,4-butylene glycol-dimethyl carbonate), and (2) a reaction product of poly(1,6-hexanediol-adipic acid) and poly(1,4-butylene glycol-dimethyl carbonate).
7. The adhesive composition of claim 1, wherein the at least one acrylic polymer compound comprises one or more of: polylauryl acrylate; polybutyl acrylate; poly(2-ethylhexyl) acrylate; poly(ethyl acrylate-2-ethylhexyl acrylate); polylauryl methacrylate; an acrylic copolymer made from two or more monomers, the two or more monomers comprising methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, methyl methacrylate, acrylic acid, methacrylic acid, styrene, vinyl acetate, butadiene, and a mixture of one or more thereof.
8. The adhesive composition of claim 1, wherein the at least one solvent is ethyl acetate, methyl ethyl ketone, and a mixture of one or more thereof.
9. The adhesive composition of claim 1, wherein the adhesive composition is used to form a laminate having an oxygen permeability of less than 750 cubic centimeters per [square meter-day].
10. A method for producing a crystalline polyester-polycarbonate-based polyurethane adhesive composition for producing an adhesive laminate structure, the method comprising mixing: (a) at least one isocyanate component, wherein the at least one isocyanate component is selected from the group consisting of: polyisocyanates based on xylene diisocyanate; polyisocyanates based on hexamethylene diisocyanate; polyisocyanates based on diphenylmethane diisocyanate; polyisocyanates based on toluene diisocyanate; and (b) at least one isocyanate-reactive component, the at least one isocyanate-reactive component comprising a blend of: (bi) 15 wt % to 45 wt % of at least one crystalline polyester-polycarbonate diol compound, based on the total weight of the isocyanate-reactive components; (bii) 0.05 wt % to 4 wt % of at least one acrylic polymer compound, based on the total weight of the isocyanate-reactive component; and (biii) 10 wt % to 90 wt % of at least one solvent, based on the total weight of the isocyanate-reactive component.
11. A multi-layer laminated product, comprising: (A) at least the first layer; (B) at least a second layer; and (C) at least one layer of a cured adhesive according to claim 1 disposed intermediate the first layer and the second layer; wherein the cured adhesive bonds the first layer to the second layer; and provides a laminate having an oxygen transmission rate (OTR) of less than 750 cubic centimeters per [square meter-day].
12. A method for producing a multi-layer laminated product, the method comprising the steps of: (I) applying the adhesive according to claim 1 to at least a portion of the surface of the first layer and / or the second layer; (II) contacting the first layer with the second layer such that the adhesive is disposed between the first layer and the second layer; as well as (III) curing the adhesive to form a multi-layer laminate product, including bonding the first layer to the second layer via the cured adhesive.
13. A packaging container product comprising the laminate according to claim 11.
Citation Information
Patent Citations
Single-pot process for the production of polyester-co-carbonate polyols
CN104220476A
Method of making laminates having reduced oxygen permeability
US20160230046A1